PENGARUH PARTISIPASI PENYUSUNAN RENCANA BISNIS ANGGARAN (RBA), KOMITMEN ORGANISASI, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA UNIVERSITAS BENGKULU - Sari, Kartika Mayang; Abdullah, Abdullah (Universitas Bengkulu, 2016)
The research was aimed to examine and obtainempirical evidences of the influence of budgetparticipation bussiness plan, commitment oforganization, and motivation of work toperformance official at the University of Bengkulu.This research used a purposive sampling. Thesample was used in the research was 65 respondentsof official at the University of Bengkulu. The data inthis study was the primary data that has obtainedfrom the directly spread questioner to therespondens. The questionnaire distributed to 59which can be analyzed. The multiple linearregression analysis was used to analyze thehypothesis with SPSS 16 program.The result of this study explained that budgetparticipation bussiness plan, commitment oforganization, and motivation of work were positiveaffected to performance official at the University ofBengkulu.